Roofing slate standards: A critical review. (15th July 2016) - Cárdenes, Víctor; Cnudde, Jean Pierre; Wichert, Jörn; Large, David; López-Mungira, Aurora; Cnudde, Veerle
Highlights: Roofing slate is the natural stone with the third-largest production by volume. There are several standards regarding slate, most important are EN 12326 and ASTMC406 . The two most common test methods are water absorption and bending strength. Results may differ due to differences in the way tests are performed. Abstract: Roofing slate has its own regulations and standards, as with other natural stones. The two main markets for roofing slate are USA/Canada and Europe. Given the very long tradition of slate mining in these two areas, it is no surprise that the first regulations for roofing slate were developed there. In the USA and Canada, the technical requirements are compiled in the standard ASTMC406, while in Europe test methods and requirements are defined in EN 12326. There are also standards from China (GB/T 18600) and India (IS 6250), the emerging production countries in the slate market. This review article analyses and compares the current test methods for roofing slate. Also, new test methods are proposed in order to complement the information of the official standards.